Design, modeling, and evaluation of a doublet heat extraction model in enhanced geothermal systems. (May 2017) - Xia, Yidong; Plummer, Mitchell; Mattson, Earl; Podgorney, Robert; Ghassemi, Ahmad
Abstract: A conceptual Enhanced Geothermal System (EGS) model, where water is circulated through a pair of parallel injection and production wells connected by a set of single large wing fractures, is designed, modeled, and evaluated in this work. The water circulation and heat extraction in the fractured reservoirs is modeled as a fully coupled process of fluid flow and heat transport. Using a newly developed, open-source, finite element based geothermal simulation code, FALCON, simulation results were obtained for a 30-year operation at a depth of 3 km and geothermal gradient of 65 ° C per km of depth. With a sensitivity study of the heat production to the design parameters, preferable fracture horizontal spacing, downward deviation angle of the parallel wells, and injection flow rate are recommended. Upscaling calculations of the developed EGS model have shown that, an industrial production-level system may be achievable if it consists of 40 equidistant fractures that connect two 1.2 km long parallel well sections with a well separation of 500 m; and if a system of these dimensions operates for 30 years at a flow rate of 0.1 m 3 /s, with an electric power output at least 5 MW and pumping power of less than 1 MW. In particular, the performance metrics demonstrated in this work match well with those suggested by others, thus indicating the general applicability of our conceptual models. Highlights: A new EGS heat extraction model is designed, modeled, and evaluated. A newly developed and validated open-source geothermal simulation code is employed. The sensitivity of reservoir heat production to key EGS design parameters is analyzed. Based on the new model, design parameters for industrial-level power supply are suggested.